Kualitas Mikrobiologi Dendeng Asap Dengan Menggunakan Daging Yang Berbeda Pada Pengasapan Dengan Serbuk Medang - Jaya Putra Jahidin (Fakultas Peternakan Universitas Jambi, 2014)
The objective of this research was to study the characteristics of beef and buffalo meat as raw materials of smoked dendeng and the use of medang sawdust. Parameters observed during research were microbiology variables (total plate count, S. aureus, molds). The design of the experiment was Complete Randomized Design with three replications. Nonparametric data of organoleptic tests was processed statistically by Kruskal-Wallis method. Parametric data physical, chemical and microbiological variable analyzed by t test (Steel and Torrie 1993). Data processing using the program Statistical Analysis System (SAS) 9.1 and Minitab 15 version. The results of this study indicate that; microbiological characteristics of dendeng asap using medang sawdust in general is still quite good until 7 days of storage.